The impact of cognitive performance on quality of life in individuals with Parkinson's disease - Maira Rozenfeld Olchik; Annelise Ayres; Marcieli Ghisi; Artur Francisco Schumacher Schuh; Carlos Roberto Mello Rieder (Dementia & Neuropsychologia)
ABSTRACT Background: Evidence points to the occurrence of cognitive impairment in all stages of PD, constituting a frequent and debilitating symptom, due to high impact on quality of life and mortality of patients. Objective: To correlate cognitive performance with quality of life in PD. Methods: The sample was drawn from a Movement Disorders Clinic of a reference hospital in Porto Alegre. Inclusion criteria were: PD diagnosis, according to the United Kingdom Parkinson's Disease Society Brain Bank criteria for idiopathic PD (Hughes et al. 1992) and patient consent to participate. Patients with other neurological pathologies and those submitted to deep brain stimulation were excluded. The evaluation consisted of a cognitive testing battery (composed of eight tests for assessing cognitive performance), and a questionnaire on quality of life (PDQ-39) and depression (BDI). Results: The sample comprised 85 individuals with PD, with a mean age of 62.9 years (±10.7), mean disease duration of 10.4 years (±5.7), and mean educational level of four years (±4.3). There was a significant relationship between total score on the PDQ and all cognitive tests, showing that poor cognitive performance was correlated with poor quality of life. Moreover, a significant correlation was observed between cognitive tests and depression, H&Y, education level, and age. Conclusion: It may be concluded that the individuals with PD in this sample showed a correlation between poorer quality of life and worse cognitive performance. Poor performance was also correlated with more advanced stage, older age, low level of education and depression.